Liturgical Minitexts as Clues to the History of a Manuscript: The Case of Vercelli - Brusa, Gionata (Scrineum, 2025)
There are more than forty manuscripts in the Vercelli Chapter Library that can be dated before the tenth century. Some of them are of local origin, others were produced in North Italy, others are of either Frankish or German provenance. These differences in production offer evidence for relationships that linked the bishops of Vercelli, mainly during the tenth and early eleventh centuries, with high-ranking ecclesiastical figures from beyond the Alps. Over the centuries several of these manuscripts received either annotations, or pen trials, often linked to the liturgical sphere and provided with musical notation (e.g. verses from the Psalter or short chants sung during the Mass or the Office). These minitexts can reveal a great deal to us: through the analysis of their content, such as their handwriting, textual variants, and musical notations, it is possible to formulate new hypotheses about the provenance of selected manuscripts among the Vercelli group, their history, and the route that brought them to Vercelli.